Occurrence of Metals in Nepal: A Brief Review - G.C., Rajendra Bahadur (International Journal of Applied Sciences and Biotechnology, 2013)
In Nepal, fairly good amounts of different types of minerals have been reported. More than 85 minerals and their varieties have been known in large concentration in Nepal. The minerals which occur in Nepal is sizeable amounts have not been fully exploited. It is believed that there are areas in Nepal which contain plenty of tentalum, niobium, molybdenum, and rare earth metal ores. Nepal may become a major supplier of these metals if their proper execution is made. Alluvian plains of Nepal are known to have placer gold while the middle region contains copper, iron, zinc, nickel, cobalt etc. A few deposits of lead, zinc and iron have been reported in the snow-capped areas. Economic deposits of iron ore are noticed in phulchoki, near Kathmandu valley. This article gives the summary for the occurrence of most important metals in Nepal. Some important applications of these metals are also included here. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9175 Int J Appl Sci Biotechnol, Vol. 1(4): 176-179